Multifarious approaches of implementation to transfer gender sensitivity in health care practice: a scoping review - Judith Mollenhauer; Sophia Sgraja; Ute Seeland; Martina Kloepfer; Volker E. Amelung; Clarissa Kurscheid (BMC Health Services Research, 2025)
Abstract Background Gender-sensitive care (GSC+) is part of patient-centered care and necessary for adequate patient outcome. Implementation measures are needed to close the gap between evidence-based medicine and nursing and lacking gender-sensitive daily care. The present scoping review is part of the German Innovation Fund project HeartGap (funding number: 01VSF22030), is registered in the German Register of Clinical Studies (clinical trial registry number: DRKS 00031317, registration date: 24.02.2023), and aims to identify measures, facilitators, and barriers to enhance a sustainable implementation process of GSC+. Methods Literature was identified from PubMed, web of science and CINAHL (2008–2023). The relevance of 23,508 articles was assessed and content analyzed. The systematic search, snowball principle, and hand search brought a total of 117 articles. The included articles were subsumed in one of the four derived main dimensions (i) politics, (ii) research/science, (iii) education, and (iv) institutions of care. The implementation of GSC+ in institutions of care (inner setting) is dependent on outer factors such as political decisions, education, or research/science (outer settings). Results The results demonstrate facilitators and barriers, which influence the implementation of GSC+. Key measures regarding main dimensions are described as follows: (i) Politics provides the framework for the implementation of GSC+. Lobbying is a useful instrument to enhance awareness of politics. Learning from international best-practice concepts and promoting career advancement facilitates the implementation. (ii) Generating evidence by conducted studies enables the integration of GSC+ content through professional associations in guidelines. (iii) Educating (future) health care providers through GSC+ training programs, journal clubs and mandatory integration into the curricula enhances awareness of patient´s diversity. (iv) For implementing changes in daily care routine, the implementation process should be accompanied and structured by change agents. A handbook on how to organize quality circles facilitates the change process. Conclusion The implementation of GSC+ is a cross-dimensional task. There are already many measures that can sustainably improve gender sensitivity in the dimensions. There is still a lack of compulsory requirements for implementation and recommended actions to ensure that GSC+ is considered in practice.